1991
DOI: 10.1088/0031-9155/36/8/002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound attenuation and texture analysis of diffuse liver disease: methods and preliminary results

Abstract: A study was performed to find and test quantitative methods of analysing echographic signals for the differentiation of diffuse liver diseases. An on-line data acquisition system was used to acquire radiofrequency (RF) echo signals from volunteers and patients. Several methods to estimate the frequency-dependent attenuation coefficient were evaluated, in which a correction for the frequency and depth-dependent diffraction and focusing effects caused by the sound beam was applied. Using the estimated value of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 31 publications
3
59
0
Order By: Relevance
“…Assuming a homogeneous tissue model, the am plitude spectrum of the backscattered echo signal re ceived in pulse-echo mode, E ( ƒ, z ) , is a random vari able (indicated in bold) with Rayleigh-distributed am plitudes, and an average value, ¡i(f, z ), that can be described by a linear model (Oosterveld et al 1991): (2 ) where E (f, z) is the received amplitude at temporal frequency ƒ of the backscattered echoes of a small tissue volume at depth z, P 2( f ) is the acoustoelectric transfer function of the transducer, D 2(f, z) is the dif fraction spectrogram of the transducer, T (/, z) is the tissue transfer function, and S (f) is the backscatter function.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming a homogeneous tissue model, the am plitude spectrum of the backscattered echo signal re ceived in pulse-echo mode, E ( ƒ, z ) , is a random vari able (indicated in bold) with Rayleigh-distributed am plitudes, and an average value, ¡i(f, z ), that can be described by a linear model (Oosterveld et al 1991): (2 ) where E (f, z) is the received amplitude at temporal frequency ƒ of the backscattered echoes of a small tissue volume at depth z, P 2( f ) is the acoustoelectric transfer function of the transducer, D 2(f, z) is the dif fraction spectrogram of the transducer, T (/, z) is the tissue transfer function, and S (f) is the backscatter function.…”
Section: Theorymentioning
confidence: 99%
“…The absolute TC (o n foam) was estimated using a method well known in the literature (Insana et al 1983;Oosterveld et al 1991). The procedure is as follows: Place a volume o f the medium in a water tank and orient its planar surface perpendicular to the beam axis.…”
Section: Transducer Characteristics Estimationmentioning
confidence: 99%
“…At 3.5MHz, for an average speed of sound of 1500 m/s in human soft tissues, this corresponds to wavelength λ=430µm, which is of the order of magnitude of the liver microstructures. The spectrogram ) , ( z f S of the RF signal at frequency f and at a distance z from the probe is generally modelled as [3][4]: Regarding the generation of non-specular reflection in a homogeneous tissue, the backscattering spectrum is often modeled as…”
Section: Methodsmentioning
confidence: 99%
“…Liver is the most frequent example. The in vivo characterization of this organ is often restricted to its attenuation properties and it has been proved that the ultrasonic attenuation coefficient increases as the amount of pathological fat in the liver increases (Oosterveld et al, 1991;Lu et al, 1999). Also, the study of excised cancer tissue revealed the differences in acoustic attenuation among cancer types and degrees of pathology.…”
Section: Introductionmentioning
confidence: 99%